Effect of Work Life Balance on Job Satisfaction to Improve Employee Performance (PT. Agro Muko) - Adi Sismanto; Ivan Haristo (Penerbit Jurnal Indonesia, 2024)
This study aims to determine the effect of work life balance and reward system on employee job satisfaction at Pt.Agro Muko Estate. The sample used in this study amounted to 65 people. In this study the authors used data collection methods by means of observation, questionnaires and interviews. Based on the results of this study, it states that work life balance (X1) has an effect on job satisfaction (Y) in using the product, this can be seen from the results of research conducted with a path coefficient of 0.780 while the reward system (X2) has an effect on job satisfaction (Y) in using the product. It can be seen from the results of the research conducted that is equal to 0.821, and Job Satisfaction (Y) on Employee Performance (Y1) at PT Agro Muko. This can be seen from the efficiency β of 0.567 or 56.7% with a significant level of 0.000 <0.050, then H0 is rejected, which means that there is a positive and significant effect between Work Life Balance on Employee Performance.